The impact of data breaches on corporations and the status of potential regulation and litigation. Issue 4 (1st October 2020) - Klaus, Tim; Elzweig, Brian
Abstract : Data breaches can have large effects on organizations as their information systems are compromised. This paper examines data breaches and the impact of data breaches on the stock price of corporations. Furthermore, this paper examines the regulatory framework of data breaches and both legal issues and the impact of cases in this area. The findings are summarized and future research in this area is proposed.